Urinary C-peptide creatinine ratio as a non-invasive diagnostic tool for differentiating type 1 from type 2 diabetes mellitus in adult Emirati population: a prospective validation study - Alshamsi, Fayez; Pathan, Afrin; Yasin, Javed; Sharma, Charu; Alshemsi, Hussain Abdalla; Alblooshi, Abdelrahman; AlAwadhi, Mohamed Abdulkareem; Alali, Ahmad Abdulrazak; Alkuwaiti, Maitha; Afandi, Bachar; AlKaabi, Juma; Agha, Adnan (Frontiers in Endocrinology, 2025)
AimsThe precise differentiation between Type 1 diabetes mellitus (T1DM) and Type 2 diabetes mellitus (T2DM) can be challenging in clinical practice, particularly in adults. We aimed to validate the diagnostic accuracy and performance of urinary C-peptide creatinine ratio (UCPCR) for distinguishing T1DM from T2DM in the Emirati population.MethodsThis prospective cross-sectional study included 79 patients with diabetes (19 T1DM, 60 T2DM) from Tawam Hospital Diabetes Center, UAE. Post-prandial urine samples were collected for UCPCR measurement using chemiluminescent immunoassay. Receiver operating characteristic (ROC) analysis determined optimal cut-offs. Multivariable logistic regression and cost-comparison analyses were performed.ResultsMean UCPCR was significantly lower in T1DM compared to T2DM (0.29 ± 0.64 vs 1.44 ± 1.82 nmol/mmol, p<0.001). ROC analysis revealed that a UCPCR cut-off of <0.25 nmol/mmol achieved 100% sensitivity and 91.7% specificity for T1DM diagnosis (AUC 0.991, 95% CI: 0.978-1.000). In patients with diabetes duration <5 years, UCPCR maintained excellent discrimination (AUC 0.988, sensitivity 100%, specificity 91.7%). However, specificity declined in patients with a diabetes duration of >10 years (82.4%), with 15% of these longstanding T2DM patients exhibiting UCPCR values <0.25 nmol/mmol, reflecting progressive beta-cell decline. Multivariable regression identified UCPCR (OR 0.001; 95% CI: 0.000–0.012; p<0.001) as the strongest independent predictor of T1DM. Cost-comparison analysis demonstrated ≥ 90% cost reduction when compared with serum C-peptide or autoantibody panels.ConclusionsUCPCR < 0.25 nmol/mmol accurately identifies T1DM in the Emirati population. This cost-effective, non-invasive test could improve clinical practice through enhanced diagnostic accuracy and reduced healthcare costs.